(untitled) (Journal of Academic Research, 2025)
The thin films of the system Si10Ge10AsxTe80-x (where x = 5 and 15) prepared at 80°C were studied in the temperature ranges of 200, 300, and 400oC. The two multilayers of thin films consist of silicon (Si), germanium (Ge), and tellurium (Te) doped with arsenic (As). Annealing temperature was varied to investigate its effect on the structural and electrical properties of the films. The crystalline structure and the influence of annealing on the structure were investigated by X-ray diffraction. The X-ray data of films annealed at 400°C illustrated some crystallizing Ge-Ge phases. The optical band gap decreasing of arsenic-doped films was found. It has been shown that with increasing arsenic content in the films, their conductivity also increases. The optical measurements showed that the optical energy gap Eg decreases and/or increases upon annealing, while the increase is partially due to crystallization effects. Regarding the electrical measurements, they were carried out at different annealed temperatures and annealing times. The results showed that band gap energy decreases from 2.49 to 1.22 eV with respect to the rise of As content. Moreover, the incorporation of arsenic leads to a decrease in the activation energies of crystallization and an increase in the conductivity. The activation energies of crystallization of the As-(15nm) and As-(45nm)-doped systems Si10Ge10AsxTe80-x are 16.9 and 11.5 kJ/mol, respectively.